hlyM, a transcriptional silencer downstream of the promoter in the hly operon of Escherichia coli. - Jubete, Y (1995)
Transcription of the hly operon of transmissible plasmids in Escherichia coli is subject to a tight regulation which also involves various chromosomal genes, such as hha. We have identified a 200-bp region within the hlyC gene, designated hlyM, which modulates hemolysin expression. The deletion of hlyM increased the activity of hly::galK fusion 20-fold. hlyM does not contain any internal promoter, nor is it capable of acting in trans. Our data suggest that the chromosomal Hha protein interacts with hlyM in order to silence the hly promoter. In addition, hlyR, a positive activator of hemolysin expression, seems to suppress the modulatory effect dictated by the Hha protein on the hlyM region.